Customer Relationship Management Practices and Employee Sensitivities of Private Sector Banks: An Analysis in Indian Context - Sultana, Mehbooba; Mpanme, Ditalak; Ahmed, Jaynal Uddin (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This paper aims to scrutinize bank employees’ perspectives on customer relationship management (CRM) practices in the banking sector, particularly private sector commercial banks operating in Goalpara District of Assam, India. The research plan consists of experimental in nature whereby different aspects of CRM in the banking sector have been extracted from the previous literature and tested on a sample size 24 number of employees working in the banks selected taking 3 each from 8 branches. Based on Bank Service Quality (BSQ) scale, variables were selected and analysed with the help of descriptive statistics and ranking analysis of identified parameters was utilized with the help of the Garret ranking technique. The study found that the loan facility and ATM facility along with service variety are found as the major product-related factors; timely services with trustworthy behaviour of the employees and the quality of services along with procedural simplicity and convenience is the most important service-related factors for evolving an effective CRM practice. The employee perceptions on the personal relationship of the bank officials with their customers’ staples in selecting the banks and retaining the customers.